Gender gaps across the earnings distribution in Britain: are women bossy enough? - Yekaterina Chzhen; Karen Mumford (Institute for the Study of Labor (IZA), 2009)
This paper investigates gender differences between the log wage distributions of full-time British employees in the public and private sectors. After allowing for positive selection into full-time employment by women, we find significant and substantial gender earnings gaps, and evidence of glass ceilings, in both sectors. The earnings gaps amongst the higher income earners are found to be related to there being a scarcity of senior women in high skilled, white-collar occupations, especially in the public sector.
urn:nbn:de:101:1-20090909287
Keywords: J3; J7; 330; Gender; earnings; wage-gap; selection; distribution; Lohndifferenzierung; Lohnstruktur; Frauenarbeitslohn; Weibliche Führungskräfte; Privatwirtschaft; Öffentlicher Dienst; Großbritannien